Analisis Pengaruh Ekspor, Impor, Kurs, Investasi, dan Belanja Negara Terhadap Pertumbuhan Ekonomi di Indonesia - Martinus, Titan; Budiman, Johny (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2024)
Economic growth is an important indicator in calculating and analyzing a country's development progress. This research aims to test and analyze how important export, import, currency, investment and government spending factors are to economic growth in Indonesia. This research uses secondary data with data in the form of time series originating from several official websites of Indonesian government inst. The data management method uses panel data regression with a fixed effect approach in the 2018-2022 time period with calculating total 60 data within quarter every year in 2018-2022. The results of this research show that the variables exports, investment and state spending have a significant effect on economic growth, while the import and currency variables do not have a significant effect on economic growth.